Imaging Review of the Posterior Cruciate Ligament - Cook, Cristi Reeves; Wissman, Robert D. (The Journal of Knee Surgery, 2021)
Posterior cruciate ligament (PCL) injuries can often be missed on physical examination, especially in multiligament knee injuries. Therefore, a comprehensive approach to imaging the PCL should be implemented whenever history and examination findings indicate relative risk. Radiography, including a posterior-stress view, and magnetic resonance imaging, when available, provide consistently accurate diagnosis of PCL pathology and common knee comorbidities. Computed tomography and ultrasonography can be useful modalities with potential advantages with respect to availability and access, specific comorbidities, and/or cost-effectiveness.
Keywords: radiology; magnetic resonance imaging; computed tomography; ultrasonography; posterior cruciate ligament